The evaluation of the effect of periodic resistance training along with vitamin D3 consumption and mesenchymal stem cell transplantation on cortical TNF-β levels in streptozotocin-induced diabetic rats - Behrooz Mohammadnezhad; Seyed Abdollah Hashemvarzi (Medical Laboratory Journal)
Background: Inflammation plays a major role in the development and progression of diabetes. Vitamin D deficiency and physical inactivity can also increase the risk of developing type 2 diabetes. Combined therapeutic strategies are promising approaches for the treatment and prevention of diabetes. This study aimed to investigate the effects of resistance training, vitamin D3 supplementation, and adipose-derived mesenchymal stem cell (MSC) transplantation on tumor necrosis factor-beta levels in the cerebral cortex of diabetic rats. Methods: Eighty male Wistar rats (Weighing 290±19 g) were randomly divided into 10 groups: healthy control, sham, diabetes, training, vitamin D, MSC, training+vitamin D, MSC+training, MSC+vitamin D, and training+MSC+vitamin D. Training groups were subjected to a resistance training program on a ladder. MSC groups received 1.5 × 106 MSCs, and vitamin D supplementation groups received 1 microgram/kilogram of vitamin D3 eight times. Cortical TNF-β levels and fasting serum glucose levels were measured. Results: After six weeks, the combination of resistance training with vitamin D3 supplementation and MSC transplantation (P=0.018), as well as the combination of resistance training with MSCs (P=0.024), significantly reduced the diabetes-induced elevation of TNF-β levels. Conclusion: Resistance training with appropriate intensity, duration, and recovery between exercise sessions, combined with MSC transplantation and vitamin D3 supplementation, has profound anti-inflammatory effects on the cerebral cortex tissue of diabetic rats. This type of intervention, especially the transplantation of MSCs, may be a promising protective strategy against some complications of diabetes.